Legal Exception in The Practice Of Detentioning Criminal Action for Violence on Children - Herri Hendra; Ismansyah Ismansyah; Aria Zurnetti (Wacana Hukum, 2020)
The issue of certainty because it is always associated with the law, provides the consequence that legal certainty here always questions the legal relationship between citizens and the state. As a value, legal certainty is not merely always related to the state, because the essence of legal certainty is a matter of protection from the arbitrary actions of the authorities. The existence of legal certainty is a hope for justice seekers of the arbitrary actions of law enforcement officers who sometimes are always arrogant in carrying out their duties as law enforcers. Because with the existence of legal certainty the public will know the clarity of their rights and obligations according to law. Without legal certainty, people will not know what to do, do not know what is right or wrong, are prohibited or not prohibited by law. This legal certainty can be realized through a good and clear naming in an Act and the application will also be clear